Let z = 28 - 26. Solve 0*c + z*c = -10 for c.
-5
Let n(j) = 2*j**2 - 23*j - 36. Let v be n(13). Solve z + 5 - v = 0 for z.
-2
Suppose 0 = 36*j - 34*j - 12. Solve 0 = 2*b - 0*b - j for b.
3
Let b(x) = x3 + 6*x2 + 5*x + 2. Let z be b(-5). Solve z*u + 4 = -4 for u.
-4
Let i be -13(1 + 1). Let s be (6/(-12))/(1/i). Solve 0 = -s*n + 4*n + 4 for n.
-4
Let t = -1 + 3. Suppose 0 = -t*g + 1 + 3. Let n be g/(-3) + 11⁄3. Solve -n*b + 3 + 0 = 0 for b.
1
Let z = -19 - -21. Solve 0 = -o + z*o for o.
0
Let y = -22 + 13. Let r = y + 15. Solve -4*m + r*m + 8 = 0 for m.
-4
Let f = 31 + -23. Solve -4*n - 4 - f = 0 for n.
-3
Let n(o) = o2 - 7*o + 7. Let b be n(7). Let q(j) = j3 - 6*j**2 - 7*j + 2. Let v be q(b). Solve 0*p = -v*p - 2 for p.
-1